REJUVENATION AND GERIATRIC CONSIDERATION IN PREVENTIVE, PROMOTIVE AND SOCIAL CONCEPT OF HEALTH CARE (International Journal of Ayurveda and Pharma Research, 2017)
Ayurveda having holistic approach aims at prevention, promotion, preservation and also cure from the disease. Everyone wants to give the impression of being young forever and increases life-span by staying healthy. Ageing, a complex and inevitable process begins before birth and continues through entire life span. The strength of Ayurveda in the context of Geriatric care is Rasayana therapy Rasayana i.e., rejuvenation therapy is one of the most important branch of Astangayurveda. As the incidence of elderly people is rising in the population worldwide including India. In India 3.8% of the population are older than 65 years of age. Rasayana therapy deals primarily with geriatric problems to improve their quality of life and remain self dependent for their daily activities to maximum possible extent. Moreover it is necessary to rejuvenate the body system for a better harmony of the body, mind and soul. Rasyana therapy has considerable scope to develop a safe and cost effective protocol for geriatric care. Moreover in Ayurvedic texts, there are given many ways in prevention and promotion of health. Various regimens like Dincharya (daily regimen), Ritucharya (seasonal regimen), Rasayana therapy (rejuvenation), Sadvritta (rules & regulations of ideal routine)and Achara Rasayana(code of conduct) along with Yogic practices are utmost important factors to maintain a healthy life style and happy psychological set up.